2014
DOI: 10.1155/2014/634945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Correlation of Cell Cycle Proteins and Ki-67 Interaction in Paranasal Sinus Inverted Papilloma Prognosis and Squamous Cell Carcinoma Transformation

Abstract: The recurrent sinonasal inverted papilloma (IP) could be transformed to sinonasal squamous cell carcinoma. We use protein expression patterns by immunohistochemical method to see whether the expression of p53, p16, p21, and p27 belongs to cell-cycle-regulators and PCNA (proliferating cell nuclear antigen) and Ki-67 the proliferation markers in sixty patients with sinonasal inverted papilloma, and 10 of them with squamous cell carcinoma transformation. Significantly elevated levels of Ki-67, p27, and PCNA in IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Immunohistochemical studies established the benign nature of the proliferation, and the overall histologic pattern was also most an inverted squamous papilloma. The Ki67 proliferation index was vanishingly low (<1%), in contrast to that encountered in squamous dysplasias and malignancies of the conjunctiva and recurrent sinonasal papillomas that harbor squamous cell carcinomas or synchronous carcinoma 14,15,20. For example, dysplastic squamous conjunctival lesions have a significantly higher Ki67 proliferation index of 25-45 percent than that in the current case.…”
contrasting
confidence: 62%
“…Immunohistochemical studies established the benign nature of the proliferation, and the overall histologic pattern was also most an inverted squamous papilloma. The Ki67 proliferation index was vanishingly low (<1%), in contrast to that encountered in squamous dysplasias and malignancies of the conjunctiva and recurrent sinonasal papillomas that harbor squamous cell carcinomas or synchronous carcinoma 14,15,20. For example, dysplastic squamous conjunctival lesions have a significantly higher Ki67 proliferation index of 25-45 percent than that in the current case.…”
contrasting
confidence: 62%
“…The PCNA, Ki-67 and p27 could interact with CDK1 (Cyclindependent kinase 1-a key player protein in cell cycle regulation) and promote the cell entry into the cell cycle with consequent proliferation and cancerization. Tsou et al [36] in a recent study on a cohort of 70 patients observed significantly elevated levels of Ki-67, p27, and PCNA in SNIPs with sinonasal SCC transformation compared with SNIPs without malignancy. Other authors have revealed that the nuclear immunoexpression of the inhibitor of apoptosis protein survivin and Bcl-2 oncoprotein immunoexpression are significantly higher in SNIP, suggesting that survivin and Bcl-2 may be involved in sinonasal tumorigenesis [37].…”
Section: Ki-67 Pcna Bcl-2mentioning
confidence: 94%
“…Some authors found an increased proliferative activity of tumor cells (significantly higher Ki-67), an elevated expression of PCNA (proliferating cell nuclear antigen), and a decreased expression of p27 in SNIPs with severe dysplasia and invasive SCC [36]. The PCNA, Ki-67 and p27 could interact with CDK1 (Cyclindependent kinase 1-a key player protein in cell cycle regulation) and promote the cell entry into the cell cycle with consequent proliferation and cancerization.…”
Section: Ki-67 Pcna Bcl-2mentioning
confidence: 99%
“…Ultimately, a total of 17 studies fulfilled the above select criteria and were included in the current meta-analysis. [9,2338] Among the 17 articles published in English, the publication years ranged from 1998 to 2015. Sixteen studies including 229 SNSCC and 675 benign papilloma patients evaluated the relationship between p53 expression and SNSCC in cancer versus benign sinonasal papillomas.…”
Section: Resultsmentioning
confidence: 99%